German consumers’ attitudes toward artificial meat - Jacobs, Anne-Katrin; Windhorst, Hans-Wilhelm; Gickel, Julia; Chriki, Sghaier; Hocquette, Jean-François; Ellies-Oury, Marie-Pierre (Frontiers in Nutrition, 2024)
The aim of this study was to analyze the impact of sociodemographic characteristics on willingness to try (WTT), regularly eat (WTE), or pay (WTP) for artificial meat, its expected societal challenges and general acceptance as well as its future potential development in Germany. Answers to an online questionnaire by 3,558 potential German adult consumers were evaluated. About 63% of the respondents thought this novel food was promising/acceptable. The vast majority (70%) stated that they would be willing to try it, with the most important drivers being ethics, curiosity and eco-friendliness. Around 57% of the participants said they would be willing to eat artificial meat regularly. Most of the respondents (40%) were willing to pay the same price for artificial as for conventional meat.In terms of its future potential, almost 75% of respondents believed that this new product would become commercialized in more than five years and that it was perceived as a solution that is both more ethical (67%) and more environmentally friendly (58%) than traditional meat. In addition, there were significant impacts of demographic factors on the willingness to engage with artificial meat. For example, high WTT and WTE were found among young male respondents (18-30 years of age), males that rarely consumed meat or had a low income (< €1,500). This also applied to the female respondents, who, however, belonged to higher income classes. Young German consumers with a high level of education or income up to €3,000 as well as consumers who did not eat meat had a high WTP for this novel food. In addition, respondents' positive opinion and acceptance of artificial meat had a positive influence on WTT and WTP. These results are important for the discussion of a paradigm shift in global meat production with respect to sustainability, demand for meat and the adoption of new food products.